Efficacy and safety of peripheral magnetic stimulation for the treatment of intractable hiccups after stroke: a prospective, blinded, parallel randomized controlled clinical trial - Liu, Qiliang; Jiang, Yijia; Sun, Jingbo; Liu, Huiyu; Chen, Junbin; Jiao, Chenze; Chen, Daiyi; Liu, Zicai (Frontiers in Neurology, 2025)
AimsPreclinical studies indicate that magnetic stimulation may be an efficacious treatment for intractable hiccups in post-stroke patients. This study aimed to investigate repetitive peripheral magnetic stimulation (rPMS) potential efficacy and safety for treating intractable hiccups.MethodsThis randomized controlled trial randomly assigned 60 patients with stroke with intractable hiccups to receive rPMS (n = 30) or metoclopramide (n = 30). The control group received a 10 mg metoclopramide injection intramuscularly twice daily, while the experimental group underwent daily repeated magnetic stimulation at 5 Hz with 1,200 stimuli using a round coil transversally positioned below the xiphoid process. Metoclopramide or rPMS was administered until the hiccups were entirely ceased. The efficacy of the two groups was evaluated after 1 week of treatment.ResultsAll 60 enrolled male patients completed the study. The proportion of patients achieving complete cure was significantly higher in the magnetic stimulation group than in the metoclopramide group (23/30 vs. 15/30; p = 0.032). However, total response rate (cure + improvement) did not differ significantly between groups (29/30 vs. 28/30; p = 1.000). No significant differences were observed in recurrence rates (p = 0.052). Just one case of fatigue and one case of dizziness were observed in the metoclopramide group.ConclusionMagnetic stimulation may be superior to metoclopramide in achieving complete cure of intractable hiccups after stroke, though both treatments show high overall response rates.Clinical trial registrationhttps://www.chictr.org.cn/, ChiCTR2200060435.